INTERAKSI KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR GO PUBLIK DI BEI - Widiana, Resha Novi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to test empirically the influence of the cash flow statement components (operating cash flow, investment, and funding), gross profit, return on investment (ROI), and economic value added (EVA) to the stock return. Multiple linear regressions is used in this research and the samples are 13 food & beverages companies which are go public in Indonesia Stock Exchange in the period of 2009 until 2012. This research is conducted in Indonesia Stock Exchange Corner STIESIA Surabaya. The analysis instrument that is used in this research is SPSS version 21.0 program. The result that has been obtained is based on the goodness of fit test shows that the regressions model is feasible to used to predict the influence of operating cash flow (PAOit), investment cash flow (PAIit), funding cash flow (PAPit), gross profit (PLKit), return on invesment (ROI), and economic value added (EVA) to the dependent variable that is stock return (Rt) at food and beverages companies which are go public in Indonesia Stock Exchange in the period of 2009 until 2012. By using the determination coefficient test (R2) has a strong contribution. Partially the hypothesis test only generates gross profit variable (PLKit) which has no significant influence and it has negative tendency to the stock return (Rt).Keywords: operating cash flow, investment cash flow, funding cash flow, gross profit, return on investment, economic value added and stock return.